1996
DOI: 10.1055/s-0038-1650639
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Oxidized Low Density Lipoproteins and von Willebrand Factor in Chronic Renal Failure

Abstract: SummaryAn ELISA specific for a wide spectrum of oxidized apo B-100 in OxLDL was developed and applied to blood samples from 27 control subjects, 20 mild chronic renal failure (MCRF) patients, 21 severe chronic renal failure patients on conservative treatment (SCRF) and 56 severe chronic renal failure patients on maintenance hemodialysis (HEMO). Mean levels of OxLDL were 0.59 mg/dl in controls (95% Cl, 0.52-0.66 mg/dl), and were 2.7-fold (p <0.01), 3.1-fold (p <0.001) and 5.4-fold (p <0.001) higher in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
122
3
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 159 publications
(128 citation statements)
references
References 29 publications
1
122
3
2
Order By: Relevance
“…15 Standard preparations of MDA-modified and copper-oxidized LDL were prepared as described elsewhere 16,17 and were used as assay control subjects. 10 Characterization of modified LDL involved measurement of thiobarbituric acid-reactive substances, determination of electrophoretic mobility on 1% agarose gels, quantification of cholesterol and fatty acids by high-performance liquid chromatography on a Nova-Pak C18 reversed-phase column (Waters Associates), and quantification of proteins by Lowry assay and of phospholipids by enzymatic assay (Biomérieux). 18 Oxidized LDLs were isolated from the purified LDL fractions of patients by fast flow chromatography on a mono-QSepharose column.…”
Section: Lipoproteins: Isolation and Modificationmentioning
confidence: 99%
See 4 more Smart Citations
“…15 Standard preparations of MDA-modified and copper-oxidized LDL were prepared as described elsewhere 16,17 and were used as assay control subjects. 10 Characterization of modified LDL involved measurement of thiobarbituric acid-reactive substances, determination of electrophoretic mobility on 1% agarose gels, quantification of cholesterol and fatty acids by high-performance liquid chromatography on a Nova-Pak C18 reversed-phase column (Waters Associates), and quantification of proteins by Lowry assay and of phospholipids by enzymatic assay (Biomérieux). 18 Oxidized LDLs were isolated from the purified LDL fractions of patients by fast flow chromatography on a mono-QSepharose column.…”
Section: Lipoproteins: Isolation and Modificationmentioning
confidence: 99%
“…We have demonstrated that the specificity of the mAb E6 depends on the extent of protein modification only. 10 All lipoprotein concentrations were therefore expressed in terms of protein.…”
Section: Lipoproteins: Isolation and Modificationmentioning
confidence: 99%
See 3 more Smart Citations